Legal and organizational features of the development of self-government in the Republic of Kazakhstan - Aitimov, B.Zh.; Nurbek, D.T. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of the study is to determine the historical and traditional concepts of the national foundations of local self-government in the Republic of Kazakhstan with an emphasis on the theory and practice of local self-government, analyze the main problems of local self-government development at the present time, identify the main barriers in the formation of its national model and provide the necessary legislative proposals for its improvement. The article reveals the importance of the development of local self-government in the country at the present time, analyzes the issues considered when developing its national model, and considers relevant legislative proposals. As a result of the application of the historical-dialectical method, the continuity of the history of the formation of local self-government in Kazakhstan and its insufficient development is revealed. In addition, during the study, a legal analysis of the existing legislation on local self-government was carried out and gaps in its components were identified by the synthesis method. In addition, during the study, a legal analysis of the existing legislation on local self-government was carried out and gaps in its components were identified by the synthesis method. To fully analyze the development of local self-government in other countries, its interface with the Kazakh experience, a comparative legal analysis was also carried out. As a result of the research, with the help of legal analysis, the legislative and organizational problems of local self-government are systematized, proposals for legislation have been developed to improve it. Having stud-ied the topic, the unaccounted moments in the improvement of local self-government in Kazakhstan were identified and the national, historical, and regional features of its development were considered.